Pathologists' Perceptions Regarding Oropharyngeal Specimens during Covid-19 Pandemic - Mahrukh Sheikh; Marium Zaheer; Syeda Sadia zafar; Saba Hassan Shamim; Arsala Urooj; Lubna Avesi; Lubna Avesi (ziauddin University, 2024)
Background: The Covid-19 pandemic effected individuals worldwide. A significant number of specimens examined by pathologists are obtained from oropharyngeal region containing a highly viral titer along with increased preference of the virus to these tissues compared to other areas of the body requiring. The need of knowledge, attitudes such as appropriate Personal Protective Equipment (PPE) along with discarding of samples and adherence to protocols while dealing with these samples is necessary. Therefore, we aimed to assess the knowledge, attitude and practices of oral pathologists pertaining to modifications in laboratory protocols issued by various international organizations. Methods: A validated questionnaire with 22 close-ended questions was given to academic faculty, practicing pathologists and trainees of the pathology department working in a government institute (n=37). Statistics were applied and p<0.05 was considered statistically significant. Results: In this study 16 (73.7%) of the individuals were found to be well aware of the possible modifications in protocols. In addition, 12 (50%) pathologists recommended the use of complete PPE while performing various procedures. Furthermore, 15 (68.2%) individuals were satisfied with their laboratory design and training to combat the possible risks of the disease. p value was found to be 0.50, which shows an insignificant association between pathologists and laboratory practices. Conclusion: The results of the study can be considered satisfactory as they indicate that 16(73.7%) pathologists dealing with oropharyngeal specimens are aware of the modified guidelines regarding laboratory protocols, handling of specimens, architecture and personal protective equipment provided by organizations such as Center for Disease Control and World Health Organization. Keywords: Covid-19 Pandemic; Pathologists; Laboratory.